1998
DOI: 10.1200/jco.1998.16.4.1414
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin plus vinorelbine, a new well-tolerated and active regimen for the treatment of extensive-stage small-cell lung cancer: a phase II study. Gruppo Oncologico Centro-Sud-Isole.

Abstract: These data show that carboplatin plus vinorelbine is an active and well-tolerated regimen in extensive SCLC. In view of the activity, low toxicity, and ease of administration, it may be a reasonable alternative to more toxic cisplatin-containing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…At the time this study was planned, single-drug efficacy of vinorelbine had been demonstrated (Gridelli et al, 1997) and the combination of carboplatin and vinorelbine was well tolerated in phase II trials (Masotti et al, 1995;Pronzato et al, 1996;Gridelli et al, 1998Gridelli et al, , 1999Santomaggio et al, 1998). Later vinorelbine/ cisplatin regimens have shown similar efficacy when compared to other cisplatin combinations with third-generation cytotoxic drugs (Schiller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…At the time this study was planned, single-drug efficacy of vinorelbine had been demonstrated (Gridelli et al, 1997) and the combination of carboplatin and vinorelbine was well tolerated in phase II trials (Masotti et al, 1995;Pronzato et al, 1996;Gridelli et al, 1998Gridelli et al, , 1999Santomaggio et al, 1998). Later vinorelbine/ cisplatin regimens have shown similar efficacy when compared to other cisplatin combinations with third-generation cytotoxic drugs (Schiller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…3 Newer agents, including the taxanes, vinorelbine, gemcitabine, topotecan, and irinotecan demonstrate significant single agent activity. [4][5][6][7][8] In the last decade, a variety of platinum-based combination therapies tested in phase III trials have failed to demonstrate an efficacy superior to that of etoposide plus cisplatin (EP). [9][10][11][12] In 2002, Noda et al 8 reported the results of a phase III trial from the Japanese Cooperative Oncology Group (JCOG) that randomly assigned 154 patients with ED SCLC to either EP (etoposide 100 mg/m 2 intravenously [IV] days 1 to 3 with cisplatin 80 mg/m 2 IV on day 1, once every 3 weeks) or irinotecan plus cisplatin (IP; irinotecan 60 mg/m 2 IV on days 1, 8, and 15 plus cisplatin 60 mg/m 2 IV on day 1, once every 4 weeks).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of carboplatin-vinorelbine in small cell lung cancer has shown a response-rate of 74% (Gridelli et al, 1998) and is currently being investigated in the UK as a treatment for those patients with small cell lung cancer with a poor prognosis. In platinum-resistant ovarian carcinoma one study found single-agent activity of the drug to be 30% .…”
Section: Other Tumoursmentioning
confidence: 99%